Hubungan Antara Self Efficacy dengan Social Loafing Mahasiswa Fakultas Psikologi Universitas Putra Indonesia “YPTK” Padang - Ane Titisemita (Pusat Kajian Demografi, Etnografi dan Transformasi Sosial, 2021)
The purpose of this study was to determine the relationship between self-efficacy and social loafing for students of the Faculty of Psychology, Universitas Putra Indonesia